An experimental optimization study for concentration and laser power effects in the fullerene-C60 and azo dye doped guest-host liquid crystal systems - Okutan, M.; Koysal, O.; San, S. E.; Yakuphanoğlu, Fahrettin (Elsevier Science Bv, 2009)
The current-voltage characteristics of a famous guest-host liquid crystal system have been investigated under dark and laser illumination conditions. Dependency of current modulation with respect to concentration and laser power gives some optimization possibilities and estimations on the reorientation mechanisms of the liquid crystals. The current-voltage character of pure E7 is almost unchanged with laser pumping, while the fullerene and dye doping are enhancing effects in their individual and collective usage. The negative resistance effect was observed for some certain concentrations of the dye and C-60, and this peculiarity is shown to be switched with laser illumination. The mobility of the doped LC samples was calculated by transient current measurements and its dependency on the dye concentration and the laser power was investigated. It is evaluated that the effect of methyl red is a critical parameter in photoconductivity applications of liquid crystals. (c) 2009 Elsevier B.V. All rights reserved
Keywords: Photoconductivity; Fullerene; Methyl red; Nematic liquid crystal